STUDY ON POET ARMANDO MENEZES RESEARCH - Prabhash Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
One may consider Indian literature written in English to be a type of by-product. For about two hundred years, English dominion was imposed on India. Not only did they leave us with a western way of life and a functioning style, but they also left us with a number of cultural influences. The consistent use of English as the language of communication is one of them. After the British Raj had been firmly established, the English had the intention of establishing schools and institutions where English would be the primary language of instruction. After Queen Victoria established her monarchy over the colonies, including India, this led to the establishment of higher education institutions in the form of universities in the cities of Calcutta, Bombay, and Madras. As a result of Lord William Bentinck’s benigh rule, the English language had already been established as India’s official language for purposes like communication, education, and government. In this context, Lord Macaulay’s Minitue is an interesting book to read.